Komunikacja matki z dzieckiem w okresie prenatalnym - Matuszczak-Świgoń, Joanna; Kowalska-Żelewska, Anna (Człowiek i Społeczeństwo, 2020)
The aim of this paper is to present theories, current research on the forms and importance of a mother’s communication with her child in a prenatal period, and discuss the results of own research in this area. In the research, the Communication with a Prenatal Child Questionnaire was used which measures six forms of prenatal communication. Prenatal communication is significant for both a mother and a child in her womb. Thanks to prenatal communication the mother can explore more consciously the challenges of pregnancy which are preparatory tasks for the role of a parent and the child develops better. The mother learns how to express her feelings non-verbally through empathy, facial expressions, touch, synchrony, and intuition. After childbirth, she can use the forms of communication from the prenatal period.